Lepidium apetalum Willd. (Brassicaceae)- A new angiospermic record for Bangladesh - Khanam, Mahbuba; Ara, Hosne (Bangladesh Journal of Plant Taxonomy, 2004)
No abstract available. Bangladesh J. Plant Taxon. 11(1): 95-98, 2004 (June)